Phenomenology and Cognitive Science: Don't Fear the Reductionist Bogey-man. Issue 2 (3rd April 2018) - Hohwy, Jakob
Abstract: Shaun Gallagher calls for a radical rethinking of the concept of nature and he resists reduction of phenomenology to computational-neural science. However, classic, reductionist science, at least in contemporary computational guise, has the resources to accommodate insights from transcendental phenomenology. Reductionism should be embraced, not feared.